Internalisasi Nilai Moderasi Beragama melalui Kebijakan Pendidikan Agama Islam - Sukari, Sukari; Yulianto, Heru Purwo (Lembaga Yasin AlSys, 2026)
The issues of religious intolerance and exclusivism pose serious challenges in educational contexts, including in Pendidikan Agama Islam (PAI), thereby necessitating policies capable of systematically internalizing the values of religious moderation in students. This study aimed to analyze the process of internalizing religious moderation values through Islamic Religious Education policy and to examine its implications for character formation and social harmony. A qualitative approach was employed using a library research method through the analysis of policy documents, scholarly articles, and relevant legislation. The findings show that PAI policy emphasizes the integration of religious moderation values, such as tolerance, balance, inclusivity, and respect for diversity through curriculum development, learning strategies, and assessment systems oriented toward strengthening moderate attitudes. The internalization process is reinforced through contextual learning, the exemplary conduct of educators, and the integration of national and religious values within intracurricular and co-curricular activities. The study concludes that comprehensively designed Islamic Religious Education policies make a significant contribution to shaping moderate religious attitudes among students and to fostering social harmony in multicultural societies. The implications of this research underscore the importance of adaptive and sustainable education policies to strengthen religious moderation as a foundation for peaceful and inclusive communal life.